2022
DOI: 10.3389/fcimb.2022.907314
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Therapy for Staphylococcus Aureus Infections: A Review of Animal Models, Treatments, and Clinical Trials

Abstract: Staphylococcus aureus (S. aureus) is a common and virulent human pathogen causing several serious illnesses including skin abscesses, wound infections, endocarditis, osteomyelitis, pneumonia, and toxic shock syndrome. Antibiotics were first introduced in the 1940s, leading to the belief that bacterial illnesses would be eradicated. However, microorganisms, including S. aureus, began to develop antibiotic resistance from the increased use and abuse of antibiotics. Antibiotic resistance is now one of the most se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 98 publications
0
34
0
Order By: Relevance
“…Since then, only a few case reports or small case studies have been published on the subject of DLI [ 9 , 16 ]. Additionally, the use of specialized and individualized phage mixtures has shown to be an alternative in the fight against multi-drug resistant bacteria as well as in persistent transplant or implant-related infections [ 11 , 16 , 17 ]. Moreover, in vitro studies have demonstrated that bacteriophages are able to disrupt certain biofilm matrices by exopolysaccharide degradation, bacterial cell infection and subsequent cell lysis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, only a few case reports or small case studies have been published on the subject of DLI [ 9 , 16 ]. Additionally, the use of specialized and individualized phage mixtures has shown to be an alternative in the fight against multi-drug resistant bacteria as well as in persistent transplant or implant-related infections [ 11 , 16 , 17 ]. Moreover, in vitro studies have demonstrated that bacteriophages are able to disrupt certain biofilm matrices by exopolysaccharide degradation, bacterial cell infection and subsequent cell lysis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these promising results, bacteriophage treatment is still not common and not officially recommended in the western hemisphere. There is a lack of real clinical trials–the known treatments rely mostly on case reports or small case studies (summarized in Plumet et al and Aslam et al [ 17 , 20 ]).…”
Section: Discussionmentioning
confidence: 99%
“…However, PMF has been ignored as a target for antibacterial agents to a sizeable extent [5]. DiSC3 (5) is a kind of fluorescent dye; changes in its fluorescence value can reflect changes in the PMF components ∆ψ and ∆pH of the cell membrane [6,12]. Fluorescence enhancement has shown increased cell membrane permeability or the ∆ψ dissipation of PMF.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of methicillin-resistant Staphylococcus aureus (MRSA) in the 1960s, the epidemic of MRSA has increased in Asia, Europe, and America [ 1 ]. The World Health Organization estimated that the number of deaths caused by drug-resistant bacterial infection is increasing yearly, and this number could probably rise to 10 million by 2050 [ 6 ]. Ciprofloxacin (CIP) belongs to the second generation of fluoroquinolone antibiotics, which has been widely favored since its listing due to its broad-spectrum antibacterial activity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another promising therapy, which in the future might be used as an adjuvant therapy for IE, is bacteriophage therapy ( Plumet et al, 2022 ). A first-in-patient case study describes a LVAD patient with a persistent open-chest S. aureus device infection ( Aslam et al, 2019 ).…”
Section: Future Directionsmentioning
confidence: 99%